Industrial structure, appropriate technology and economic growth in less developed countries - Lin, Justin Yifu 1952- (Policy research working paper, 2009)
"The authors develop an endogenous growth model that combines structural change with repeated product improvement. That is, the technologies in one sector of the model become not only increasingly capital-intensive, but also progressively productive over time. Application of the basic model to less developed economies shows that the (optimal) industrial structure and the (most) appropriate technologies in less developed economies are endogenously determined by their factor endowments. A firm in a less developed country that enters a capital-intensive, advanced industry in a developed country would be nonviable owing to the relative scarcity of capital in the factor endowments of less developed countries. "--World Bank web site